Brain-Derived Neurotrophic Factor Modulates the Effect of Sex on the Descending Pain Modulatory System in Healthy Volunteers. Issue 10 (13th March 2020) - Gasparin, Assunta; Zortea, Maxciel; dos Santos, Vinicius Souza; Carvalho, Fabiana; Torres, Iraci L S; de Souza, Andressa; Fregni, Felipe; Caumo, Wolnei
Abstract: Objectives: We investigated sex differences and the influence of brain-derived neurotrophic factor (BDNF) in the descending pain modulatory system (DPMS), as measured by change on the numerical pain scale (NPS; 0–10) during conditioned pain modulation (CPM task; primary outcome) and by function of the corticospinal motor pathway and heat pain thresholds (HPTs; secondary outcomes). Methods: This cross-sectional study included healthy volunteers ranging in age from 18 to 45 years (32 male and 24 female). Assessment included serum BDNF, HPT, change on the NPS (0–10) during the CPM task, and motor-evoked potential (MEP) using transcranial magnetic stimulation (TMS). Results: The MEP (Mv) amplitude was larger in male participants compared with female participants (mean [SE] = 1.55 [0.34] vs mean [SE] = 1.27 [0.27], respectively, P = 0.001). The mean NPS (0–10) during CPM task changed more substantially for female compared with male participants (mean [SE] = −3.25 [2.01] vs mean [SE] = −2.29 [1.34], respectively, P = 0.040). In addition, a higher serum BDNF (adjusted index for age) was associated with a larger decrease of the NPS during CPM task ( P = 0.003), although further regression analyses by sex showed that this was only significant for females ( P = 0.010). Conclusions: Significant sex differences were identified in DPMS function and corticospinal motor pathway integrity. Nevertheless, BDNF was associated with the function of the DPMS in female but not male participants, indicating that sex and neuroplasticity state are crucial factors for pain perception in healthy subjects.